Sistema informático para la gestión de los procesos en la central ecuatoriana de servicios agrícolas de Saquisilí - Chancusi Guamán, Myriam Ximena (2017)
This technological proposal analyzed the situation in which the Ecuadorian Central of Agricultural Services is placed for this it is proposed to improve the management of document management processes, which through an analysis and study several problems were observed when performing the management of their processes manually, Since this does not have systematized mechanisms that help the management of the processes and projects that are carried out in the institution. That is why it is necessary to manage this information of processes. The objective is to help organize the information in a suitable way through a web application that facilitates the management of the processes that are developed in the Ecuadorian Central of Agricultural Services. The methodology used is SCRUM which allows to organize properly the work during the development cycle. And it is also a process of the methodology to minimize risks during the realization of the project, but in a collaborative way works with the incremental iterative model which divides the system into several iterations that are small systems which, when joined, form a single Project. For the development of the application we used the tools like HTML, PHP these programming tools work with the Model, Vista, Controller, to get a better user experience, We used BootStrap which is a framework or set of open source tools for web site and application design, finally as storage medium was considered the use of MySql database engine. The acquired results were successful by means of the analyzes that were carried out in the cases of tests of the system the library and the inventory looks for and generates the necessary reports, that the user needs, the projects generate a summary and the percentage of progress of each of the processes that are carried out with their respective results.